PENGARUH QUANTUM LEARNING TERHADAP SIKAP DALAM MENCEGAH HIV-AIDS PADA REMAJA MA DI PONDOK PESANTREN MIFTAHUL ULUM SUREN KABUPATEN JEMBER - Siswoyo Siswoyo; Latifa Aini S.; Nurul Muftofiah Roisatin (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
The high prevalence of HIV-AIDS can lead to a decrease of productive age number in Indonesia. This problem can be attributed to the risk to high school adolescent, as one of the risk group for HIV-AIDS infection. This infection risk can be declined by health education. Quantum learning is the appropriate education method for adolescent. This study aims to identify the attitude of high school teenager in preventing HIV-AIDS before and after quantum learning intervention. The research method was pre-experimental research using one group pre and post test design. Sample was selected using probability sampling method and stratified random sampling technique. The sample were 39 students. The Data analyzed usedwilcoxon test with α< 0,05. The result showed were the attitude in preventing HIV-AIDS before intervention was 21 person (53,8%) positive attitude and 18 person (46,2%) negative attitude while the attitude in preventing HIV-AIDS after intervention was 31 person (79,5%) positive attitude and 8 person (20,5%) negative attitude. There was a significant attitude in preventing HIV-AIDS of adolescent at Miftahul Ulum Suren Islamic senior High School change (p=0,004, 95% CI) after quantum learning intervention. Based on the findings, it is imperative to improve attitude on HIV-AIDS prevention factors of senior high school teenager. It is also important to improve guided supervision and conseling ability from teacher. Keywords : to prevent HIV/AIDS, attitude, adolescent, quantum learning.